Macrophytes’ abundance changes in eutrophicated tropical reservoirs exemplified by Salto Grande (Brazil): Trends and temporal analysis exploiting Landsat remotely sensed data - Coladello, L.F.; de Lourdes Bueno Trindade Galo, M.; Shimabukuro, M.H.; Ivanova, Ivana; Awange, Joseph (2020)
© 2020 Elsevier Ltd